2021
DOI: 10.1016/j.rmed.2021.106481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-invasive respiratory support on gas exchange and outcomes in COVID-19 outside the ICU

Abstract: Non-invasive respiratory support (NRS) outside of the ICU has played an important role in the management of COVID-19 pneumonia. There is little data to guide selection of NRS modality. We present outcomes of NRS outside the ICU and discuss the effects of NRS on gas exchange with implications for management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…A total of 6394 relevant studies were obtained from the databases. After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 6394 relevant studies were obtained from the databases. After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were considered to have an unclear risk of bias. The 20 observational 9 , 11 19 , 21 23 , 25 , 27 32 studies were assessed using the NOS checklist, and the results are shown in the Table 2 . All studies were of medium quality (⩾5 stars) or above, and 10 were considered high quality (⩾8 stars).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in all the hospitals that participated in the study, patients were treated in monitored areas by skilled teams. A study conducted in Ireland with a similar design compared oxygen therapy, positive pressure, and HFOT: an improvement in arterial blood gases was documented mainly in patients transitioned from oxygen to CPAP but without differences on mortality both in patients with and without DNI order ( 63 ).…”
Section: Non-invasive Support Modalities Escalating Algorithms and The Role Of Combined Therapiesmentioning
confidence: 99%